Hypothetical Structuralism - Czakon, Marcin (Ruch Filozoficzny, 2022)
Michael Resnik suggests a new version of structuralism which he calls non-ontological structuralism. In the present short article, I discuss this view-point in the context of the Frege-Hilbert controversy about meaning of primitive notions in deductive theory, with special regard to the original views of Ajdukiewicz, Hilbert’s student. Following the proposed differentiations, I introduce a new type of structuralism which I call hypothetical structuralism, close to Resnik’s non-ontological structuralism.